2016 ASE undergraduate essay competition candidate information. (15th June 2017) - Chen, Alice
Abstract: The aim of this review is to discuss the role of medicaments and materials used in teeth undergoing root canal treatment and how they affect the overall prognosis of root canal treated teeth. Irrigants, medicaments and materials play a vital role in RCT. They reduce the overall microbial load within the root canal system, help reduce inter‐appointment pain, and induce apexification during RCT of permanent teeth with immature apices. In addition, they also help create a hermetic coronal and periradicular seal to entomb any residual microorganisms within the canals and prevent future ingress of contaminants into the root canal system and subsequent reinfection. Whilst the role of various materials in RCT has been thoroughly investigated, the available literature and longitudinal clinical studies evaluating the affect of such materials on the prognosis of RCT is scarce, and requires further investigation.